A Feminist Critical Discourse Analysis of Gendered Representations in Nepal’s Grade XI Compulsory English Textbook - Panday, Nikesh (Ganeshman Darpan, 2026)
The study employs Critical Discourse Analysis (CDA) and Feminist Critical Discourse Analysis (FCDA) to Nepal’s Grade XI Compulsory English textbook, for interrogating the construction of gender across selected readings, literary texts, and routine language-learning tasks included in the book. Using Fairclough’s (1992, 1995) three-dimensional model (text, discursive practice, and social practice) and Lazar’s (2005) FCDA approach to guide the analysis, the study demonstrates how the textbook both creates conditions for, and simultaneously limits, feminist meanings. The findings illustrate a strong counter-discourse telling the subject position of rights-bearing women and girls, particularly in advocacy and civic texts, as collective agents. But feminist resonances are not evenly distributed: repetitive requests for practitioners in classrooms and aspirations professed within institutions also cultivate patriarchal common sense, including the denigration of women’s housework through a moral regulation of marginalized mothers. This paradox can be better managed through a critical textbook pedagogy that rebels against the linear structure of dominant patriarchal narratives and passes as a measurable literacy skill (agency, evaluation, voice, and legitimization). The study concludes with practical pedagogical and assessment recommendations relevant to critical literacy goals.